TWO SONGS OF FRIENDSHIP: The Convergence of Judeo-Christian and Nuu-chah-nulth Philosophies of Friendship in the Narrative Space of the 21st Century - Kilian, Bożena (Review of International American Studies, 2013)
TO BE ADDED